2007
DOI: 10.1902/jop.2007.060339
|View full text |Cite
|
Sign up to set email alerts
|

The Additional Effect of a Dentifrice on the Instant Efficacy of Toothbrushing: A Crossover Study

Abstract: The use of a dentifrice did not contribute to mechanical plaque removal during manual toothbrushing. It seemed that the mechanical action provided by the toothbrush was the main factor in the plaque-removing process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
50
0
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(52 citation statements)
references
References 30 publications
0
50
0
2
Order By: Relevance
“…To include a population with high plaque scores at the start of the experimental period, participants were selected that had an overnight plaque score of 2 or higher as assessed according to Modified Quigley & Hein Plaque index (Paraskevas et al, 2007). Exclusion criteria were: oral mucosal lesions, orthodontic appliances, removable (partial) dentures, and overhanging margins of dental restorations (clinically assessed with a periodontal probe), the use of antibiotics during the last 6 months, Dutch Periodontal Screening Index (Mantilla Gomez et al, 2001) (DPSI) ≥3+ (periodontal pockets >5 mm with bleeding on probing and gingival recession), the use of medication possibly influencing normal gingival health, pregnancy and smoking.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To include a population with high plaque scores at the start of the experimental period, participants were selected that had an overnight plaque score of 2 or higher as assessed according to Modified Quigley & Hein Plaque index (Paraskevas et al, 2007). Exclusion criteria were: oral mucosal lesions, orthodontic appliances, removable (partial) dentures, and overhanging margins of dental restorations (clinically assessed with a periodontal probe), the use of antibiotics during the last 6 months, Dutch Periodontal Screening Index (Mantilla Gomez et al, 2001) (DPSI) ≥3+ (periodontal pockets >5 mm with bleeding on probing and gingival recession), the use of medication possibly influencing normal gingival health, pregnancy and smoking.…”
Section: Methodsmentioning
confidence: 99%
“…For plaque scores teeth were disclosed with a 1% erythrosine solution. Plaque was assessed at six sites per tooth on a six-point scale using the Quigley & Hein's plaque index (Quigley and Hein, 1962) as modified by Turesky et al (1970) and further modified by Lobene et al (1982), in which the absence or presence of plaque was recorded on a 0–5 scale (0 = no plaque, 5 = plaque covering more than two-thirds of the tooth surface) and described in detail by Paraskevas et al (2007). At the baseline appointment the level of oral health was assessed in the two contra-lateral quadrants that had previously been sampled for supragingival plaque using the Bleeding on Marginal Probing (BOMP) score (van der Weijden et al, 1994a,b; Lie et al, 1998).…”
Section: Methodsmentioning
confidence: 99%
“…In 2006 and 2007, Paraskevas et al 26,27 found no differences in the reduction of plaque scores using toothpastes with varying RDAs (± 80 to ± 200). Additionally, Rosema et al 22 observed that the presence or absence of toothpaste had no effect on plaque removal.…”
Section: Discussionmentioning
confidence: 95%
“…Inconclusive evidence exists in the literature with regard to the additional (beneficial) mechanical effect of a dentifrice on plaque removal. Paraskevas et al (17,18) affirm that the use of toothpaste did not contribute to mechanical plaque removal during manual toothbrushing and it seemed that the mechanical action provided by the toothbrush was the main factor in the plaque-removing process. Addy et al (19) in 80s already showed that the triclosan toothpastes containing the copolymer and chlorhexidine solution, produced significant reductions on salivary bacterial counts and to correlate it with plaque inhibitory properties of antimicrobial compounds.…”
Section: Discussionmentioning
confidence: 99%